Role of sympathetic nerve activity in the process of fainting - Iwase, Satoshi; Nishimura, Naoki; Mano, Tadaaki (Frontiers in Physiology, 2014)
Syncope is defined as a transient loss of consciousness and postural tone, characterized by rapid onset, short duration, and spontaneous recovery, and the process of syncope progression is here described with two types of sympathetic change. Simultaneous recordings of microneurographically-recorded muscle sympathetic nerve activity (MSNA) and continuous and noninvasive blood pressure measurement has disclosed what is going on during the course of syncope progression. For vasovagal or neurally mediated syncope, three stages are identified in the course of syncope onset, oscillation, imbalance, and catastrophe phases. Vasovagal syncope is characterized by sympathoexcitation, followed by vagal overcoming via the Bezold-Jarisch reflex. Orthostatic syncope is caused by response failure or a lack of sympathetic nerve activity to the orthostatic challenge, followed by fluid shift and subsequent low cerebral perfusion. Four causes are considered for the compensatory failure that triggers orthostatic syncope: hypovolemia, increased pooling in the lower body, failure to activate sympathetic activity, and failure of vasoconstriction against sympathetic vasoconstrictive stimulation. Many pathophysiological conditions have been described from the perspectives of (1) exaggerated sympathoexcitation and (2) failure to activate the sympathetic nerve. We conclude that the sympathetic nervous system can control cardiovascular function, and its failure results in syncope; however, responses of the system obtained by microneurographically-recorded MSNA would determine the pathophysiology of the onset and progression of syncope, explaining the treatment effect that could be achieved by the analysis of this mechanism.